Causes of mortality and unintentional poisoning in predatory and scavenging birds in California. Issue 1 (12th November 2014) - Kelly, Terra R.; Poppenga, Robert H.; Woods, Leslie A.; Hernandez, Yvette Z.; Boyce, Walter M.; Samaniego, Francisco J.; Torres, Steve G.; Johnson, Christine K.
Abstract : Objectives: We documented causes of mortality in an opportunistic sample of golden eagles, turkey vultures and common ravens, and assessed exposure to several contaminants that have been found in carrion and common prey for these species. Methods: Dead birds were submitted for testing through wildlife rehabilitation centres and a network of wildlife biologists in California from 2007 to 2009. Results: The leading causes of mortality in this study were collision‐related trauma (63 per cent), lead intoxication (17 per cent) and anticoagulant rodenticide poisoning (8 per cent). Elevated liver lead concentration (≥2 µg/g) and bone lead concentration (>6 µg/g) were detected in 25 and 49 per cent of birds tested, respectively. Approximately 84 per cent of birds tested had detectable rodenticide residues. The majority of rodenticide exposure occurred in peri‐urban areas, suggesting that retail sale and use of commensal rodent baits, particularly in residential and semi‐residential areas in California, may provide a pathway of exposure. Conclusions: Monitoring anthropogenic causes of mortality in predatory and scavenging bird species provides important data needed to inform on mitigation and regulatory efforts aimed at reducing threats to these populations.